Implementation of Integrative Holistic Early Childhood Education Activities in The Ceria Kertosari Playgroup - Indrawati, Denik; Kristiana, Dian; Irsad Rusdiani, Nurtina (Institut Studi Islam Muhammadiyah Pacitan, 2025)
The Ceria Kertosari Playgroup is an early childhood education institution that has been implementing holistic integrative early childhood education activities since 2022. The purpose of this study is to describe the implementation of holistic integrative early childhood education activities. This research is a descriptive qualitative study. The data in this study are data related to the implementation of holistic integrative early childhood education services. Data were obtained using interviews, observations, and documentation. Data analysis used qualitative descriptive analysis techniques, namely data reduction, data verification, data display, and conclusions. Based on the results of the study, it was concluded that the Ceria Kertosari Playgroup has organized holistic integrative early childhood education services, namely those related to education, health, nutrition, care, protection, and welfare services. The Ceria Kertosari Playgroup has also collaborated with various parties including health workers, Yogaatma Consulting and guardians. Although in its implementation there are some that are programmed or in other words included in the institution's curriculum, there are also activities that are conditional.